A Study on Youth Satisfaction and Service Alignment in Public Sports Services in Guangxi: A Digital Governance Perspective - Huang, Ying; Thanaponganan, Napatsawan; Thadanatthaphak, Yada (Journal of Posthumanism, 2025)
This study evaluates the quality of public sports services for youth in Guangxi based on a "digital technology-needs-oriented-precise provisioning" framework. Validated measurement scales were developed to assess service satisfaction and demand-supply matching degree among 1,200 youth participants across 10 cities in Guangxi. The results reveal several service deficiencies including inadequate facilities, limited service variety, and poor information accessibility, which collectively impact youth participation and satisfaction levels. While overall satisfaction scores remain moderately high, significant disparities emerge across gender and educational levels, indicating notable demand-supply mismatches. These findings demonstrate the need for improved coordination between service provision and youth requirements in Guangxi’s public sports service system. The study provides empirical evidence for understanding the current state and influencing factors of youth-oriented public sports services in the region.